2011
DOI: 10.46989/001c.20602
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Feed Efficiency in Mangrove Red Snapper, (Lutjanus argentimaculatus Forsskal 1775) Fed Practical Diets Supplemented with L-ascorbyl-2-monophosphate-Mg

Abstract: Growth and feed efficiency were determined in red snapper, Lutjanus argentimaculatus (Forsskal 1775), fed diets containing L-ascorbyl-2monophosphate-Mg (AMP). Fish (13.39±0.08 g) were fed a practical diet without vitamin C supplement for four weeks then stocked in twelve 650-l tanks at 30 fish/tank and fed one of four practical diets containing AMP at 0, 60, 180, or 540 mg/kg dry diet for 17 weeks. Survival rates in all treatments were similar (88.9-98.9%). Fish fed the 0 or 540 ppm diets had inferior final av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The growth performance of juvenile fish in the present study, in terms of SGR, was within the range observed in other euryhaline carnivorous fish [14, 28,29]. Corroborating with our results, SGR values ranging from 1.45-1.60% BW/day were reported in mangrove red snapper with an initial weight of 13.4 g after receiving a practical diet with 45.4% crude protein for 17 weeks [30]. However, the SGR of fish in this study (1.78 to 2.08%/day) was inferior to the value reported by Chi and True [9] of ∼4.33%/day.…”
Section: Discussionsupporting
confidence: 90%
“…The growth performance of juvenile fish in the present study, in terms of SGR, was within the range observed in other euryhaline carnivorous fish [14, 28,29]. Corroborating with our results, SGR values ranging from 1.45-1.60% BW/day were reported in mangrove red snapper with an initial weight of 13.4 g after receiving a practical diet with 45.4% crude protein for 17 weeks [30]. However, the SGR of fish in this study (1.78 to 2.08%/day) was inferior to the value reported by Chi and True [9] of ∼4.33%/day.…”
Section: Discussionsupporting
confidence: 90%